Residential Unit Design for Natural Ventilation in Tropical Multi-Family High-Rises With a Double-Loaded Corridor - Tantasavasdi, Chalermwat; Inprom, Natthaumporn (Nakhara : Journal of Environmental Design and Planning, 2023)
This research investigates practical methods to improve the efficiency of natural ventilation in residential units of multi-family high-rises without additional areas. Typical studio- and one-bedroom-types of small units were redesigned using: 1) air post, 2) transom window, 3) buffer space with one corridor opening and 4) buffer space with two corridor openings. The simulation study using a CFD program to reveal that the indoor average air velocity coefficient (Cv ) in the best redesigned case (0.46) significantly improves from the base case (0.01). The paper demonstrates an example of application to an actual climate in Bangkok, Thailand. It was found that the proposed redesign using buffer spaces can considerably help upgrade the living conditions of the occupants in terms of both thermal comfort (24 hours vs. 0 hours in the comfort zone per day) and indoor air quality (24 hours vs. 8–17 hours that pass the minimum ventilation requirement per day) in the transitional month of February.